2021
DOI: 10.2319/070620-610.1
|View full text |Cite
|
Sign up to set email alerts
|

Novel three-dimensional methods to analyze the morphology of the nasal cavity and pharyngeal airway

Abstract: Objectives To assess the intraexaminer and interexaminer reliabilities of novel semiautomatic methods to segment the nasal cavity (NC) and pharyngeal airway (PA) and to determine the minimal cross-sectional area (CS) and hydraulic diameter (HD) of the PA. Materials and Methods To test reproducibility, two examiners analyzed the NC and PA independently in 10 retrospectively selected cone beam computed tomography (CBCT) images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The main purpose of this study was to precisely evaluate changes in NC and PA morphology following RME treatment at long-term follow-up using an innovative and validated evaluation method. 21 Many studies have reported that RME seems to enlarge the nasal airway, including the NC and nasopharynx. 18,23,24 However, a recent systematic review and meta-analysis showed that long-term stable results could not be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of this study was to precisely evaluate changes in NC and PA morphology following RME treatment at long-term follow-up using an innovative and validated evaluation method. 21 Many studies have reported that RME seems to enlarge the nasal airway, including the NC and nasopharynx. 18,23,24 However, a recent systematic review and meta-analysis showed that long-term stable results could not be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the airway dynamics and the risk of upper airway resistance and risk of obstruction/collapse, we used two additional upper airway outcome variables: 8) The minimal cross-sectional area of the upper airway (CS) and 9) the minimal hydraulic diameter (D H ) [ 36 ]. Both CS and D H and are indicators of the upper airway intra-luminal space.…”
Section: Methodsmentioning
confidence: 99%
“…The shape of the upper airways is mostly irregular and not round. This change in shape greatly influences the CS, whereas the D H may, to a greater extent, take into account the change in shape throughout the upper airways, which is an argument for including both measures [ 36 ]. Importantly, the positions of the minimal D H and the minimal CS do not necessarily coincide in the same upper airway positions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The segmentation was performed following the same method as described elsewhere [25]. Landmark definitions for the dental, skeletal, and airway parameters, as well as plane definitions, are presented in Table 1.…”
Section: Cbctmentioning
confidence: 99%